Characterization of farms in terms of proximity to the natural state and in terms of their contribution to landscape connectivity - CGIAR Research Program on Water, Land and Ecosystems (2017)
Data has been collected for 24 farms in Sierra del Rosario Biosphere Reserve. Data is being analyzed and results will be shared with farmers and project partners